SUBJECTIVITY IN STEPHEN DEDALUS, THE MAIN CHARACTER IN JAMES JOYCE’S A PORTRAIT OF THE ARTIST AS A YOUNG MAN - Sari, Anisa Rahmatika; Mugijatna, Mugijatna (Universitas Muhammadiyah Surakarta, 2020)
Subjectivity is a philosophical concept of how one, as a subject, gains the sense of identity through the interaction with the external world. The theorization on the conception of subjectivity itself has ranged from the early modern thinkers to post-modern thinkers. This research’s objectives are to describe the struggle of Stephen Dedalus, the main character in James Joyce’s novel entitled A Portrait of The Artist As A Young Man, to gain his identity as a form of subjectivity, and to describe how the model of subjectivity is reflected through the character of Stephen Dedalus. This research is a descriptive qualitative library research with philosophical approach using Descartes, Kant, Freud and Lacan theories. From the analysis, first, it is found out that Stephen Dedalus underwent a journey of figuring himself out through a series of events that profoundly shape his sense of identity. The involvement of many external factors like the field of art, religion, and nationality is important in constructing Stephen Dedalus’ subjectivity. Secondly, by taking into account the theorization on the idea of subjectivity from the early modern philosophers such as Rene Descartes and Immanuel Kant, to the post-modern philosophers such as Sigmund Freud and Jacques Lacan, it can be seen that Stephen Dedalus’ stream of consciousness as the main tool in perceiving his journey of life embodies the early modern conception that subjectivity is grounded on one’s independent consciousness. Keywords: subjectivity, modernity, philosophy